Influence of linear flow velocity of uncracked ammonia (NH3) gas on formation of higher nitrides, -MoN and -Fe2N, under concentrated solar irradiation in the SF40 solar furnace at PSA - Shohoji, Nobumitsu (2020)
ABSTRACT: Nitriding experiments for powder specimens of Mo and Fe were carried out using a solar furnace SF40 at PSA (Plataforma Solar de Almería) in Tabernas (Spain) in uncracked ammonia NH3 gas (NH3 gas with suppressed extent of dissociation by flowing) aiming at determining the range of linear velocity v of NH3 gas flow to yield higher nitride phases, δ-MoN for Mo and ε-Fe2N for Fe. Standard solar exposure duration at a specified reaction temperature T was set to be 60 min over range of v between 1.14 mm·s-1 and 11.4 mm·s-1. By X-ray diffraction (XRD) analysis, presence of δ-MoN was detected besides γ-Mo2N and metallic Mo for Mo powder specimen heated to 900 ºC in NH3 gas flow at v = 1.14 mm·s-1 but XRD peaks identifiable as δ-MoN became indiscernible when v was increased to 11.4 mm·s-1. On the other hand, for Fe powder specimen exposed to NH3 gas flow at v = 1.14 mm·s-1 at T = 500 ºC, remnant metallic α-Fe was detectable by XRD at the down-stream side of the specimen holder but no metallic α-Fe was detected at the up-stream side of the specimen holder suggesting that chemical activity a(N) of N atom in uncracked NH3 gas tended to decrease along the NH3 gas flow path on going from the up-stream side to the down-stream side.